Predicting asphyxia in term fetus - Alev Esercan; İsmail Demir (Taylor & Francis Group, 2023)
This aim of this study was to investigate maternal hematological laboratory parameters of term infants before birth diagnosed with asphyxia compared to mothers of healthy term infants and predict asphyxia by these parameters. This study was conducted on 109 and 192 mothers of the fetus with asphyxia and healthy, respectively. Laboratory parameters of complete blood count, including PDW (platelet distribution width), PCT (procalcitonin) and NLR (neutrophil/lymphocyte ratio), were recorded before birth from pregnant women. PDW and basophil counts were significantly higher in the asphyxia group than healthy group (p: .000). The cut-off level of 19.425 accurately predicted the occurrence of asphyxia (AUC = 0.724 (95% confidence interval 0.65-0.78), p = .000). Basophil count could predict asphyxia, especially the cut-off level of> 0.15(10³/μL) (AUC = 0.67) (95% confidence interval 0.60-0.74, p = .000). To predict asphyxia before labor, a cheap and routine test of PDW can be used after more research in this area.IMPACT STATEMENT What is already known on this subject? Asphyxia is still an unsolved problem in neonatal mortality and morbidity, and it is seen in babies of mothers who carry some risks during pregnancy (such as multiple pregnancy, baby of mother with preeclampsia, meconium aspiration, diabetes); however, it is known that it is a subject that is still not fully understood as it can also occur as a result of labor that does not have any risk factors and goes well. What do the results of this study add? In term fetuses without risk factors, it can be predicted to a certain extent whether the fetus will be diagnosed with asphyxia from the hemogram test that can work from the blood of the mother before birth. What are the implications of these findings for clinical practice and/or further research? In clinical practice, asphyxia can be estimated with a cheap and simple test, without any extra examination, by looking at the routine blood tests taken from the mother before going into labor.